2007
DOI: 10.1016/j.ydbio.2006.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of odontogenesis in Dmp1-deficient mice by targeted re-expression of DMP1 reveals roles for DMP1 in early odontogenesis and dentin apposition in vivo

Abstract: Dentin matrix protein 1 (DMP1) is expressed in both pulp and odontoblast cells and deletion of the Dmp1 gene leads to defects in odontogenesis and mineralization. The goals of this study were to examine how DMP1 controls dentin mineralization and odontogenesis in vivo. Fluorochrome labeling of dentin in Dmp1-null mice showed a diffuse labeling pattern with a 3-fold reduction in dentin appositional rate compared to controls. Deletion of DMP1 was also associated with abnormalities in the dentinal tubule system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
141
1
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 116 publications
(146 citation statements)
references
References 52 publications
(60 reference statements)
1
141
1
3
Order By: Relevance
“…While the immunohistochemical pattern of DMP1 has been clearly elucidated in mice dentin (Feng et al 2003;Lu et al 2007), no correlative TEM and fluorescence data have been available on human sound dentin. DMP1 accumulates along the peritubular dentin wall of human sound dentin, similarly to what has been previously reported in mice (Lu et al 2007), thus suggesting a functional role in their formation and maintenance (Baba et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the immunohistochemical pattern of DMP1 has been clearly elucidated in mice dentin (Feng et al 2003;Lu et al 2007), no correlative TEM and fluorescence data have been available on human sound dentin. DMP1 accumulates along the peritubular dentin wall of human sound dentin, similarly to what has been previously reported in mice (Lu et al 2007), thus suggesting a functional role in their formation and maintenance (Baba et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Cooperative interactions between DMP1 and type I collagen can initiate apatite nucleation and mineral deposition (He & George 2004, He et al 2005. Recently, in vivo studies by Lu and coworkers (Lu et al 2007) revealed that DMP1-null mice show abnormalities in mineralization and structural organization of dentin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A full-length mouse DMP1 cDNA was obtained by digesting the DMP1-pBC-KS+ construct [9] with EcoRI restriction enzyme, and the released DMP1 cDNA fragment was subcloned into a mammalian expression vector, pcDNA3.1. The DMP1-pcDNA3.1 construct was used to transfect a human embryonic kidney cell line, HEK-293, or a murine preosteoblastic cell line, MC3T3-E1.…”
Section: Generation Of Mouse Dmp1 Cdna Constructmentioning
confidence: 99%
“…Findings from Dmp1 knockout mouse experiments and gene mutation studies on human osteomalacia strengthen the conclusion that DMP1 plays an important role in bone and dentin mineralization [5][6][7]. In addition to its direct role in biomineralization, studies indicated that DMP1 may regulate osteoblast-specific and/or odontoblast-specific genes [8,9]. More recent studies indicated that DMP1 may also be involved in the regulation of phosphate homeostasis through fibroblast growth factor 23 (FGF23), a newly identified hormone that is released from bone and targeted in the kidneys; deletion of the Dmp1 gene leads to a dramatic increase of FGF23 mRNA in osteocytes [7].…”
mentioning
confidence: 94%